2014
DOI: 10.1542/peds.2013-2927
|View full text |Cite
|
Sign up to set email alerts
|

Role of Guidelines on Length of Therapy in Chorioamnionitis and Neonatal Sepsis

Abstract: BACKGROUND AND OBJECTIVE: Chorioamnionitis (CAM) is a major risk factor for neonatal sepsis. At our institution, neonates exposed to CAM and intrapartum antibiotics are treated with prolonged antimicrobial therapy if laboratory values are abnormal despite a sterile blood culture. Recently, the Committee on the Fetus and Newborn (COFN) recommended a similar strategy for treating neonates exposed to CAM. Our objective was to determine the frequency of abnormal laboratory parameters in term and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 28 publications
1
92
1
2
Order By: Relevance
“…It is also proved that funisitis / chorioamnionitis is associated with a higher risk of neonatal sepsis (21)(22). However, some researchers claim that the histological diagnosis of chorioamnionitis is not important in the prediction of newborn's further quality of life, especially if these newborns get adequate treatment and care (23)(24). Our study has shown the association between the increased CRP levels in mother's blood serum and histologically confirmed intrauterine infection, as well as congenital infection.…”
Section: Discussionmentioning
confidence: 50%
“…It is also proved that funisitis / chorioamnionitis is associated with a higher risk of neonatal sepsis (21)(22). However, some researchers claim that the histological diagnosis of chorioamnionitis is not important in the prediction of newborn's further quality of life, especially if these newborns get adequate treatment and care (23)(24). Our study has shown the association between the increased CRP levels in mother's blood serum and histologically confirmed intrauterine infection, as well as congenital infection.…”
Section: Discussionmentioning
confidence: 50%
“…46 In addition, many newborns are treated with antimicrobial agents for prolonged periods despite negative blood culture results. 5,6 Since administration of antimicrobial agents oftentimes is accompanied by admission to a neonatal intensive care unit (NICU), a large number of newborns are additionally exposed to the NICU environment where there is increased risk of acquiring infections with multi-drug resistant bacteria. Infants in NICUs are also separated from their families, which may have consequences for mother-infant attachment and successful breastfeeding.…”
Section: Review Of the Current Understanding Of Chorioamnionitismentioning
confidence: 99%
“…Comparable data for EOS of all causes also reflect a reduction in attack rate, from 2.0 – 2.5 in the late 1980s and 1990s 2325 to 0.8 – 1.0 per 1000 live births since 2005 26, 27 . Among infants ≥ 34 28 or ≥ 35 29, 30 weeks gestation or with birth weights > 2500 g 26 , recent EOS rates are only 0.5 – 0.8 per 1000 live births. These much lower attack rates reflect a landscape that is fundamentally different from that extant when consensus guidelines for neonatal sepsis management were being developed 20 years ago.…”
Section: The Evolution Of Neonatal Sepsis Risk Assessmentmentioning
confidence: 99%